Βελτιστοποίηση χαρακτηριστικών ημι-ενεργητικής ανάρτησης οχήματος - Χρυσός, Εμμανουήλ (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Μηχανολογικών Κατασκευών και Αυτομάτου Ελέγχου. Εργαστήριο Οχημάτων, 2018)
The aim of this work is to present a comparison of the main semi active suspension systems used in a passenger car, after having optimized the suspension systems of the vehicle model in respect with ride comfort and road holding. Thus, a half car model, equipped with controllable dampers, along with a seat and a driver was implemented. Semi-active suspensions have received a lot of attention since they seem to provide the best compromise between cost (energy consumption, actuators/sensors hardware) and performance in comparison with active and passive suspensions. In this work, the semi active suspension systems studied are comfort oriented and consist of (a) the two version of Skyhook control (two states skyhook and skyhook linear approximation damper), (b) the acceleration driven damper (ADD), (c) the power driven damper (PDD), (d) the combination of Skyhook and ADD (Mixed Skyhook-ADD) and (e) the combination of the two with the use of a sensor. The half car model equipped with the above suspension systems was excited by a random road profile and a road bump, and was optimized using genetic algorithms (GA) in respect with ride comfort and road holding. This study aims to highlight how the optimization of the vehicle model could lead to the best compromise between ride comfort and road holding, overcoming their well-known trade-off. The optimum results were compared with important performance metrics regarding the vehicle’s dynamic behavior in general. In Chapter 1, an introduction in the subject and the goals of this thesis are presented. In Chapter 2, the passive suspension models are described, along with their equations. Then, a seat and human model are added to the model. In Chapter 3, the most classic semi active suspension systems are analyzed. In Chapter 4, the excitations used for the model are outlined. Two kinds of excitations are applied, a random road profile generated according to ISO 8608 and a road bump. In Chapter 5, the theory of optimization and the optimization procedure are highlighted. In Chapter 6, the results of this thesis are illustrated. The efficiency of the models studied is examined. In Chapter 7, the conclusions are drawn and future work is proposed.